Rewriting early Chinese texts - Shaughnessy, Edward L., 1952- (SUNY series in Chinese philosophy and culture., 2006)
Rewriting Early Chinese Texts examines the problems of reconstituting and editing ancient manuscripts that will revise-indeed "rewrite"--Chinese history. It is now generally recognized that the extensive archaeological discoveries made in China over the last three decades necessitate such a rewriting and will keep an army of scholars busy for years to come. However, this is by no means the first time China's historical record has needed rewriting. In this book, author Edward L. Shaughnessy explores the issues involved in editing manuscripts, rewriting them, both today and in the past